Macroeconomic Factors Affecting the Growth of Micro and Small Industries in Indonesia - Nanang Rusliana; Jumri Jumri; Arfiah Busari; Dio Caisar Darma; Jati Kusuma; Febriana Khoirun Nisa (Institute of Multidisciplinary Research and Community Service, 2026)
Micro and small industries (MSIs) play a crucial role in the national economic structure but are vulnerable to macroeconomic dynamics such as fluctuations in gross domestic product (GDP), inflation, interest rates, exchange rates, exports, unemployment, and proportion of credit and tax incentives. The instability of these economic factors can directly affect the competitiveness and resilience of MSIs, making an in-depth study of their impact highly relevant. This paper navigates the relationship between GDP, tax incentives, inflation, interest rates, exchange rates, unemployment, export value, and the proportion of credit allocated to micro industries, small industries, and MSIs as a whole. Medium-term data from 2013–2023, focusing on Indonesia, were observed using linear regression. Three main findings emerged from the analysis. First, GDP and the proportion of credit had a significant positive effect on micro industries. Second, tax incentives, interest rates, export value, and the proportion of credit had a significant positive effect on small industries. Third, the proportion of credit was the only macroeconomic factor with a significant positive effect on MSIs overall. The empirical findings suggest that access to finance is a key determinant of MSIs performance, in contrast to other macroeconomic variables, which are often anomalous or contradictory. This reality highlights that limited access to credit critically hampers MSIS investment, growth, and productivity, even under relatively stable macroeconomic conditions. Moreover, in macroeconomic policy scenarios, transmission mechanisms such as inflation or interest rates do not always have an immediate or direct impact on MSIs due to their limited access to formal financial support. Future research is expected to analyse and re-examine the dynamic determinants of MSIs development using more diverse models and data extraction methods. Keywords: micro and small industries, macroeconomics, linear regression, Indonesia.